2017
DOI: 10.5138/09750185.1963
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and antiarthritic activities of Smilax zeylanica

Abstract: <p><em>Smilax zeylanica </em>Linn has been traditionally used in the treatment of rheumatoid arthritis but, no scientific data has been published supporting the claimed ethanomedical use. This study was designed to investigate the immunomodulatory and antiarthritic activities of <em>Smilax zeylanica</em>.</p><p>Methanolic extract of <em>Smilax zeylanica </em>(MESZ) roots was tested for its immunomodulatory activity by NBT reduction test. Antiarthritic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…If pollination occurs, the plant will produce a bright red to blue-black spherical berry fruit about 5-10 mm in diameter that matures in the fall (Jena 2011). S. zeylanica also often founded in temperature zone, tropics and subtropics worldwide (Babu 2017).…”
Section: Smilax Zeylanica Lmentioning
confidence: 99%
“…If pollination occurs, the plant will produce a bright red to blue-black spherical berry fruit about 5-10 mm in diameter that matures in the fall (Jena 2011). S. zeylanica also often founded in temperature zone, tropics and subtropics worldwide (Babu 2017).…”
Section: Smilax Zeylanica Lmentioning
confidence: 99%
“…Antioxidant property of roots and rhizomes of Smilax zeylanica and concluded that the methanolic extract showed potential scavenging effect against DPPH [14].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…S. zeylanica is used ethnomedicinally for the treatment of different conditions such as abscesses, boils, dysentery, psoriasis, rheumatism, skin diseases, swellings, toothache and venereal diseases [6][7][8][9][10] . This plant is shown to exhibit several bioactivities such as antimicrobial and analgesic 11,12 , antioxidant 12,13 , cytotoxic 13 , immunomodulatory and antiarthritic 14 , anthelmintic 15 , antipyretic 16 , anticonvulsant 16 , antidiabetic 17 , cytoprotective 18 , hepatoprotective 19 , antiinflammatory 20 , antiepileptic 21 , pesticidal 22 , thrombolytic 23 , and antidepressant 24 activities. Therefore, the present investigation focused to evaluate the invivo antioxidant potential of ethanolic extract of roots of Smilax zeylanica in different screening methods.…”
Section: Introductionmentioning
confidence: 99%